The Gayo People Philosophy: Genap-Mupakat and Social Harmonization in Central Aceh - Syukri Syukri (Islamica: Jurnal Studi Keislaman, 2023)
Gayo people construct collective deliberation called Genap-Mupakat, a dynamic social harmony entity as proof of local wisdom in Central Aceh. However, many people consider Genap-Mupakat a boring and time-consuming activity. Therefore, this study aimed to examine Genap-Mupakat’s importance and significant influence on oneself and others. Data were collected qualitatively through in-depth interviews. The findings showed that Gayo people’s philosophy of Genap-Mupakat fosters togetherness and justice. The system had Islamic philosophical values and was laden with knowledge, norms, rules, and laws as a reference in collective deliberation and behavior to realize social harmony. The people must adhere to these principles to avoid conflicts and hostilities. The system stated that Gayo people have the characteristics of a republic, free, and democratic society. Therefore, the philosophy promoted orderliness in collective deliberation. The Gayo adage “tertib bermajelis, umet bermulie” means that orderliness in a meeting is a prerequisite for nobility.